Transformational Leadership of Administrators Influencing Affecting School Effectiveness under the Office of Samutprakan Primary Education Service Area Office 2 - ถนอมเพ็ชร์ สุดารัตน์; รูปสุวรรณกุล ปัทมา; กลิ่นเกษร อุษาพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the transformational leadership of school administrators under the Samut Prakan Primary Educational Service Office Area 2; 2) to investigate the school effectiveness in the same area; 3) to examine the relationship between transformational leadership and school effectiveness; and 4) to identify the transformational leadership factors of school administrators that affect school effectiveness. The sample group consisted of 302 administrators and teachers under the Samut Prakan Primary Educational Service Office Area 2, determined by Krejcie & Morgan’s table (1970). A multi-stage sampling technique was employed, involving stratified random sampling based on school size, followed by simple random sampling via a drawing method. The research instrument was a questionnaire with an Index of Item-Objective Congruence (IOC) of 1.00 for all items and a reliability coefficient of 0.94. Data were analyzed using frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation, and stepwise multiple regression analysis. The research findings revealed that: 1. The overall level of transformational leadership of school administrators was at a high level. Considering each dimension, "Inspirational Motivation" received the highest mean score, reaching the highest level, while "Individualized Consideration" received the lowest mean score but remained at a high level. 2. The overall level of school effectiveness was at a high level. The dimension with the highest mean was the "Ability to Solve Internal Problems," while the lowest mean was the "Ability to Adapt and Develop the School," both of which were at a high level. 3. The relationship between transformational leadership and school effectiveness showed a moderate positive correlation (r = .674) with statistical significance at the .01 level. The aspect most strongly correlated with school effectiveness was individualized consideration (x4), which exhibited a high level of correlation (rx4y = .708) with statistical significance at the .01 level. 4. The analysis of transformational leadership factors affecting school effectiveness indicated that "Individualized Consideration" was the most influential predictor (b = .425). The multiple correlation coefficient (R) was .742, indicating that the predictive variables could collectively explain 54.45% of the variance in school effectiveness.